2008
DOI: 10.1039/b809648a
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral density analysis and photoconducting behavior in copper(ii) phthalocyanine nanostructured thin films

Abstract: Surface morphology of copper(II) phthalocyanine (CuPc) nanostructured thin films deposited on polished silicon surface was characterized by using atomic force microscopy (AFM). Characteristic topographic parameters like fractals contribute substantially to the thin film morphology, which directly or indirectly influences the physical and optical properties. Fractal geometry and scaling concepts can concisely as well as more effectively describe the complex rough surface morphology. The power values of power sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 60 publications
3
27
0
Order By: Relevance
“…After annealing process, we obtain more homogenous structure, where grains (with larger diameter) form aggregates and flake-like structure (slightly lower RMS roughness parameter after annealing process). Similar behavior can be observed in the case of thin films deposited at different temperatures of the substrate [28,29]. The variation of RMS roughness and the grain size is smaller at lower temperature but these are significantly higher in case of higher deposition temperatures.…”
Section: Resultssupporting
confidence: 68%
“…After annealing process, we obtain more homogenous structure, where grains (with larger diameter) form aggregates and flake-like structure (slightly lower RMS roughness parameter after annealing process). Similar behavior can be observed in the case of thin films deposited at different temperatures of the substrate [28,29]. The variation of RMS roughness and the grain size is smaller at lower temperature but these are significantly higher in case of higher deposition temperatures.…”
Section: Resultssupporting
confidence: 68%
“…10, the curve for the 10 nm on the annealed gold substrate is comparable to a 6 nm thick film evaporated on gold at room temperature (see above), hence the substrate temperature does not distinctly affect the molecular orientation in this case. We note however, that distinct changes, in particular of the morphology as a function of the substrate temperature were observed for related systems [59].…”
Section: Distinguishing Between the First Layers And Thin Filmsmentioning
confidence: 90%
“…As introduced in the last section of Computational methods and plotted in Figure 2b, the initial C(q) has been determined based on measured RMS roughness for the thin film type and bulk-type and relationship between C(q) and RMS discussed by Flys et al 47 After cycling, experimental studies 54,56,58,63 have reported the RMS roughness would increase. Also, based on the study of surface morphology, 45,46,64 the absolute value of m, of the plot in Figure 2b would increase, and the intercept, I, would be decreased when the RMS roughness is increased. (m, I) values were changed to mimic the effect interface roughening due to battery cycling.…”
Section: Resultsmentioning
confidence: 99%
“…For example, an interface may look like contact perfectly with uniform contact pressure at a macroscopic view, but at a microscopic view, the surface roughness will lead to non-perfect contact and non-uniform contact stress. By assuming that surface roughness has self-affined property, [45][46][47][48] this model can calculate the real contact area at every length scale. Thus, it is important to define the length scales for the battery systems.…”
Section: After LImentioning
confidence: 99%
See 1 more Smart Citation